2021
DOI: 10.3390/su132212412
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Contribution of Citrus Orchards in Climate Change Mitigation through Carbon Sequestration in Sargodha District, Pakistan

Abstract: Adopting agroforestry practices in many developing countries is essential to combat climate change and diversify farm incomes. This study investigated the above and below-ground biomass and soil carbon of a citrus-based intercropping system in six sites (subdivisions: Bhalwal, Kot Momin, Sahiwal, Sargodha, Shahpur and Silanwali) of District Sargodha, Southeast Pakistan. Tree biomass production and carbon were assessed by allometric equations through a non-destructive approach whereas, soil carbon was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The soil carbon stock (SCS) contents per hectare was calculated as follows (Eq. (2) ) [ 9 ]: Where D is the layer depth (cm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil carbon stock (SCS) contents per hectare was calculated as follows (Eq. (2) ) [ 9 ]: Where D is the layer depth (cm).…”
Section: Methodsmentioning
confidence: 99%
“…Orchards are considered important land-use type across the globe and, are valued for their economic, ecological, and cultural importance across the world [ 9 ]. Previous studies have shown that fruit tree ecosystems, including orchards, possess soil carbon sequestration potential equivalent to forests, with a range of 240–1250 g C m −2 year −1 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are few references to studies on the biomass contained in fruit trees. However, their valuation and characterization are very important because it allows their analysis as a carbon sink [3,4], energy resource, and to relate them to costs and application rates for different products such as water, pesticides, or fertilizers [5,6].…”
Section: Introductionmentioning
confidence: 99%